Hubungan antara Kontrol Diri dan Phubbing pada Mahasiswa di Masa Dewasa Awal - Naila Hullatun Nichlah; Karelina Primavitri (Lembaga Yasin AlSys, 2026)
Self-control is an individual’s ability to regulate behavior, thoughts, and emotions so that they align with social situational demands, and low self-control is often associated with maladaptive behaviors, one of which is phubbing, namely the tendency to ignore an interlocutor in face-to-face interactions due to focusing on smartphone use. This study aimed to examine the relationship between self-control and phubbing behavior among university students in early adulthood. A quantitative approach with a correlational design was employed, involving 80 university students aged 18–25 years in Indonesia who used smartphones for at least five hours per day, selected through convenience sampling. Data were collected via an online survey using the Self-Control Scale and the Phubbing Scale, both of which have demonstrated validity and reliability, and were analyzed using Pearson’s correlation test. The results showed a significant negative relationship between self-control and phubbing behavior (r = −0.434; p < .001), indicating that the higher the level of self-control possessed by students, the lower their tendency to engage in phubbing in social interactions. These findings confirm that self-control plays an important role in reducing phubbing behavior among university students in early adulthood and underscore the need to develop self-control abilities through psychological interventions and digital literacy education in order to improve the quality of students’ social interactions amid the rapid development of communication technologies.